Safeguarding Malaysia's seafarers health and wellbeing - Ganesh, Sritheran Paneerselvam; Long, Chiau Ming * (Reach Publishing Sdn Bhd, 2024)
By Dr. Ganesh Sritheran Paneerselvam- It is well known that marine waters cover more than 70% of the Earth’s surface. More than 97% of Earth’s water supply and 90% of its habitable space rely on marine environments. Marine fisheries directly or indirectly employ over 200 million people. Moreover, over three billion people worldwide depend on marine and coastal biodiversity for their livelihoods. Fish continues to be one of the most-traded food commodities globally.